Clinical Evaluation of a Non Preserved Saline Solution - Levy, B (Canadian Journal of Optometry, 2021)
With the advent of more and more contact lens pharmaceutical care products, and the manufacture of hydrophilic lenses which, by their nature, absorb and retain fluids, the question of the sterility of contact lenses is more important than ever. This evaluation assesses the clinical efficacy of Lens Plus, a non preserved saline solution, with a variety of heat and chemical disinfection systems.